2012
DOI: 10.1111/j.1420-9101.2012.02589.x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of the role of predators in the maintenance of a genetically based polymorphism

Abstract: Polymorphisms provide one of the most useful tools for understanding the maintenance of genetic and phenotypic variation in nature. We have previously described a genetically based polymorphism in dorsal patterning that is expressed by female brown anole lizards, Anolis sagrei, which occur in Bar, Diamond and intermediate Diamond-Bar morphs. Previous studies of island populations in The Bahamas support a role for selection in maintaining the polymorphism, but the agents responsible for this selection remain un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 82 publications
(131 reference statements)
1
8
0
Order By: Relevance
“…Specifically, they suggested that heterogeneity in habitat use among females may explain why that sex is more polymorphic (Stamps & Gon, 1983). Previous work has shown that females differing in dorsal pattern occur at different perch heights (Steffen, 2010;Cox & Calsbeek, 2011;Paemelaere et al, 2011b;Calsbeek & Cox, 2012), but at least in A. sagrei and A. humilis, morphs experience similar mortality rates (Cox & Calsbeek, 2011;Paemelaere et al, 2011b;Calsbeek & Cox, 2012). In our study, we found that in 16 of 36 species studied, females were significantly more polymorphic than males.…”
Section: Discussionsupporting
confidence: 54%
“…Specifically, they suggested that heterogeneity in habitat use among females may explain why that sex is more polymorphic (Stamps & Gon, 1983). Previous work has shown that females differing in dorsal pattern occur at different perch heights (Steffen, 2010;Cox & Calsbeek, 2011;Paemelaere et al, 2011b;Calsbeek & Cox, 2012), but at least in A. sagrei and A. humilis, morphs experience similar mortality rates (Cox & Calsbeek, 2011;Paemelaere et al, 2011b;Calsbeek & Cox, 2012). In our study, we found that in 16 of 36 species studied, females were significantly more polymorphic than males.…”
Section: Discussionsupporting
confidence: 54%
“…Five others are located on small (500–1600 m 2 ) cays offshore from Georgetown, Great Exuma. Details on these populations and analyses of natural selection on various phenotypic traits are reported in a series of previous papers (Calsbeek & Irschick ; Calsbeek & Smith , ; Calsbeek , ; Calsbeek & Bonneaud ; Calsbeek, Bonneaud & Smith ; Calsbeek, Bonvini & Cox ; Calsbeek & Cox , ; Cox & Calsbeek ,b, ). The present study synthesizes a decade of mark–recapture data from these populations to compile 22 replicates of selection on males and 19 replicates of selection on females.…”
Section: Materials Methodsmentioning
confidence: 99%
“…In this context, polymorphisms can be transient (one morph has a selective advantage), balanced (the morphs are at a stable equilibrium), or dynamic (the morphs have frequency dependent selective advantage). The coexistence of morphs can be made possible by several mechanisms, such as temporal variation in the form of selection (Calsbeek, Bonvini and Cox, 2010), negative frequency-dependent selection (Sinervo and Lively, 1996;Andrés, Sánchez-Guillen and Cordero Rivera, 2002), apostatic selection (Franks and Oxford, 2011;Calsbeek and Cox, 2012), correlational selection (Brodie, 1992;Lancaster et al, 2007), hétérozygote advantage (Penn and Potts, 1999), or morph specific habitat selection (Hedrick, 1993;Chunco, McKinnon and Servedio, 2007).…”
mentioning
confidence: 99%
“…Exceptionally wellstudied cases include the rock-paper-scissor game of frequency-dependent selection in Uta stansburiana (Sinervo and Lively, 1996) and in Lacerta vivipara (Vercken et al, 2007), the temporal fiuctuations in selection imposed by predators in Anolis sagrei (Calsbeek, Bonvini and Cox, 2010;Calsbeek and Cox, 2012), as well as the intersexual differences in prédation pressures in Lampropholis delicata (Forsman and Shine, 1995). Colour polymorphism can also be related to immunocompetence and ectoparasite load in lizards, as was demonstrated in Podareis melisellensis (Huyghe et al, 2010).…”
mentioning
confidence: 99%